The influence of food on the healing of diabetic wounds and injuries: an integrative literature review (Research, Society and Development, 2020)
Diabetes mellitus (DM) is characterized as a chronic disease, in which the patient must maintain the metabolic and pathological balance through care, including an adequate diet, to maintain quality of life. The aim of this article is to identify scientific productions on the influence of food on the healing of diabetic wounds and injuries. It is an integrative literature review, the search was carried out in the databases: LILACS, SCIELO and BDENF, via VHL. 19 articles were found that met the inclusion and exclusion criteria. It was found that nursing guidance in relation to food has significantly contributed to the self-care of diabetic patients and has reduced limb amputations and the evolution of diabetes-related ulcers, in addition to being essential for the treatment and / or control of diabetes mellitus and for improving the patient's glycemic control. It is important to search for new knowledge on the part of health professionals to provide the patient with adequate guidance and involve the family's participation in the treatment of the disease, in the balance of diet, exercise practices, taking a more critical and humanized view of care with injuries to avoid possible amputations.